An annotated list of fish genetic resources of Faizabad District, U. P. - Pandey, A C (Indian Journal of Fisheries, 2011)
As many as 74 species of freshwater fishes have been recorded from FaizabadDistrict. Apart from these native ichthyofauna, some exotics like grass carp,silver carp, bighead, common carp and exotic magur have also beentransplanted in the district for aquaculture. Out of 79 fin fishes, 25 are of majorand 21 of minor commercial importance for food and game purposes whereasthe others are considered as weed or forage fish.